Intimate partner violence against HIV-positive Cameroonian women: Prevalence, associated factors and relationship with antiretroviral therapy discontinuity—results from the ANRS-12288 EVOLCam survey. (June 2019) - Fiorentino, Marion; Sagaon-Teyssier, Luis; Ndiaye, Khadim; Suzan-Monti, Marie; Mengue, Marie-Thérèse; Vidal, Laurent; Kuaban, Christopher; March, Laura; Laurent, Christian; Spire, Bruno; Boyer, Sylvie; ,
Background: Intimate partner violence in its various forms increases HIV exposure in female victims and potentially jeopardizes the HIV treatment cascade, for instance, by impeding engagement in and adherence to care. Elevated rates of HIV and intimate partner violence are reported in Central Africa. Evidence on the effect of intimate partner violence on antiviral therapy interruption is lacking in Cameroon, where only 330, 000 women live with HIV and only 19% of HIV-positive people are virally suppressed. This study aimed to assess the prevalence and factors of intimate partner violence against HIV-positive women and its relationship with antiretroviral therapy interruption ⩾1 month. Methods: The EVOLCam cross-sectional survey was conducted in 19 hospitals in the Center and Littoral regions. The study sample comprised antiviral therapy–treated women declaring at least one sexual partner in the previous year. Scores of recent emotional, physical, extreme physical and sexual intimate partner violence were built using principal component analysis and categorized under no, occasional or frequent intimate partner violence. Multivariate logistic analyses were performed to investigate the relationship between intimate partner violence and recent antiretroviral therapy interruption ⩾1 month, and associated factors. Results: Among the 894 analyzed women, the prevalence of intimate partner violence was 29% (emotional), 22% (physical), 13% (extreme physical) and 18% (sexual). Frequent physical intimate partner violence was a significant risk factor of antiretroviral therapy interruption ⩾1 month (adjusted odds ratio = 2.42 (95% confidence interval = 1.00; 5.87)). It was also associated with HIV-related stigma (2.53 (1.58; 4.02)), living with a main partner (2.03 (1.20; 3.44) and non-defensive violence against this partner (5.75 (3.53; 9.36)). Conclusion: Intimate partner violence is a potential barrier to antiviral therapy continuity and aggravates vulnerability of Cameroonian HIV-positive women. The prevention and detection of intimate partner violence by HIV services might help to reach the last "90" of the 90-90-90 targets.